Paraquat and Parkinson’s Disease: The Molecular Crosstalk of Upstream Signal Transduction Pathways Leading to Apoptosis - See, Wesley Zhi Chung; Naidu, Rakesh; San Tang, Kim (Current Neuropharmacology, 2024)
Parkinson’s disease (PD) is a heterogeneous disease involving a complex interaction between genes and the environment that affects various cellular pathways and neural networks. Several studies have suggested that environmental factors such as exposure to herbicides, pesticides, heavy metals, and other organic pollutants are significant risk factors for the development of PD. Among the herbicides, paraquat has been commonly used, although it has been banned in many countries due to its acute toxicity. Although the direct causational relationship between paraquat exposure and PD has not been established, paraquat has been demonstrated to cause the degeneration of dopaminergic neurons in the substantia nigra pars compacta. The underlying mechanisms of the dopaminergic lesion are primarily driven by the generation of reactive oxygen species, decrease in antioxidant enzyme levels, neuroinflammation, mitochondrial dysfunction, and ER stress, leading to a cascade of molecular crosstalks that result in the initiation of apoptosis. This review critically analyses the crucial upstream molecular pathways of the apoptotic cascade involved in paraquat neurotoxicity, including mitogen-activated protein kinase (MAPK), phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/AKT, mammalian target of rapamycin (mTOR), and Wnt/β-catenin signaling pathways.
Keywords: Apoptosis